STUDI MORFOLOGI IKAN MUDSKIPPERS (GOBIIDAE: OXUDERCINAE) SEBAGAI UPAYA KARAKTERISASI BIODIVERSITAS LOKAL PULAU TARAKAN - Endik Deni Nugroho; - Ibrahim; Dwi Anggorowati Rahayu; Darius Rupa (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2016)
Tarakan city has a potential local fishery resources which have not been considered and utilized optimally, one of which is fish Mudskipper / Tempakul (mudskipper). Mudskipper one of Gobiidae Family: subfamily Oxudercinae that resemble amphibians living and liked the muddy area scattered Mangrove coastal waters. One of the basic information that is needed is to know the variation of morphological characters mudskipper in Tarakan and characterization fenetic distance between populations. Morphological characters examined included morphometric studies, meristics and special characters of this fish. This research is a descriptive quantitative and qualitative descriptive, with a survey approach. This study founded four species of Mudskipper fish that live in the habitat settlements, open land, sea and mangrove and Juata areas. There are: Peripothalamus malaccensis, Periopthalmodon freycineti, Baleophthalmus boddarti and Periopthalamus barbarus. Dendogram of morphological analysis obtained by the two groups branch, that is Periophthalmus malaccensis and Periopthalmus barbarus clade with Periophthalmodon freycineti and Baleopthlamus boddarti form different branching. Grouping of mudskipper fish differentiated based on five main morphometric characters. There are: SL: standard length, HL: length of the head, FDFB: first dorsal fin base length, SDFB: second dorsal fin base length, and VFL: long ventral fins.Keywords : morphology, Mudskipper, biodiversity, Oxudercinae, relationship